A disputa ibérica pelo domínio do Rio Paraguai na segunda metade do século XVIII e a sua representação cartográfica - Mário Clemente Ferreira (Navigator)
The colonial occupation of the Paraguay River valley was mainly in the second half of the eighteenth century. In addition to seeking to identify the reasons for such a late colonial occupation, this communication intends primarily to examine how this process has developed, including the dispute between the two Iberian crowns for dominance of territory and Portuguese and Spanish cartographic production.